Thirst for Apocalyptic Whirlwinds and Creating a New World: Russian Literature of the 20th Century from the Silver Age to the Soviet Years Aesthetics - Vadim V. Polonsky (Studia Litterarum)
In the article, specific attention is paid to the factors that define the development of Russian literature at the most critical stages of the previous century. Especially, it dwells on the Russian revolution of 1917 and its most immediate consequence: creating Soviet Art. The author demonstrates that for many figures of Russian Modernism an orientation towards total social and cultural collapse was part of their aesthetic program. The Revolution mercilessly responded to this deep inner call of Russian culture. The response was received by the public in the shadow of the last book in the Bible: the Apocalypse. New Soviet literature, separated from the “bourgeois heritage” of the Silver Age, however, was deeply connected with its dystopias and phobias, catastrophic intuition and the expectation of the transformation of a Man and World where labor, science and technique should function as divine tools in the Epic Song of the Birth of New Universe. The most important stage in the process of the liberation of Russian literature from mythological constructions of Soviet avant-garde aesthetics was the Second World War. It rehabilitated a central meta-hero of great Russian classical literature, “a little person” debunked by Modernism.